Enhancing public service ethics: more culture, less bureaucracy? - Theobald, Robin (1997)
The last decade has seen mounting pressure on public sector organizations to become more "businesslike," especially to open themselves up to the play of market forces and the real needs of customers. An important component of the business ethos that is being urged on the public sector is an emphasis on organizational culture and "getting the culture right." This article looks at the relevance of the culture perspective to the problem of ethical conduct in the public sector. The concept of organizational culture is examined critically in the light of some recent examples of attempts to effect a culture change in national and local government in the United Kingdom. The article concludes that there is a fundamental incompatibility between the imposition of a market-driven philosophy and the need for the openness and accountability that are indispensable features of all public service organizations. - Reproduced
Keywords: Civil service ethics; Bureaucracy; Civil service